Lowering EphA4 Does Not Ameliorate Disease in a Mouse Model for Severe Spinal Muscular Atrophy - Poppe, Lindsay; Smolders, Silke; Rué, Laura; Timmers, Mieke; Lenaerts, Annette; Storm, Annet; Schoonaert, Lies; de Boer, Antina; Van Damme, Philip; Van Den Bosch, Ludo; Robberecht, Wim; Lemmens, Robin (Frontiers in Neuroscience, 2019)
EphA4 is a receptor of the Eph-ephrin system, which plays an important role in axon guidance during development. Previously, we identified EphA4 as a genetic modifier of amyotrophic lateral sclerosis (ALS) in both zebrafish and rodent models, via modulation of the intrinsic vulnerability and re-sprouting capacity of motor neurons. Moreover, loss of EphA4 rescued the motor axon phenotype in a zebrafish model of spinal muscular atrophy (SMA). Similar to ALS, SMA is a neurodegenerative disorder affecting spinal motor neurons resulting in neuromuscular junction (NMJ) denervation, muscle atrophy and paralysis. In this study, we investigated the disease modifying potential of reduced EphA4 protein levels in the SMNΔ7 mouse model for severe SMA. Reduction of EphA4 did not improve motor function, survival, motor neuron survival or NMJ innervation. Our data suggest that either lowering EphA4 has limited therapeutic potential in SMA or that the clinical severity hampers the potential beneficial role of EphA4 reduction in this mouse model for SMA.